PERILAKU TRASH-TALKING REMAJA DALAM GAME ONLINE DOTA 2 - Oka Candrakusuma, I Gusti Ngurah; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
Dota 2 is a popular video game that was published in 2011, this game is mainly played by people aged 16 to 21. Player’s aggressive behaviours such as trash-talking is often complained on this game. The goal of this research is to describe the aggressive behaviours of teenage gamer in Dota 2 online game. This research is using descriptive qualitative approach . The informants were selected by using purposive and snowball technique . The data were obtained by doing interview, direct observation and documentation study. The technique of analyzing the data that used in this research through several steps that was data reduction, data display and conclusion drawing . The result of this research shows that The result of this research shows that teenager’s cognitive ability define how they see trash-talking. Teenage players dare to do trash-talking because there is a computer mediation when they communicate, this has lead trash-talking to be easily done. Informants tend to be more aggressive in trash-talking when they are playing with friends they have known. Trash-talking is not only directed to enemies, but also friends or teammates. Interactions between players and their groups contributed to some trash-talking terms that were only known to them. The trash-talking that was conducted differs depend on the enemies they faced, the nationalities, ethnics, races, and religions that are often subjected to the player’s trash-talking.   Keywords : Dota 2, Trash-talking behaviour, Teenager, Online game